GH-Inhibitory Activity of Novel Somatostatin Agonists: Potential Applications in Acromegaly - Dasgupta, P. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
Acromegaly is a relatively rare debilitating disease caused by hypersecretion of growth hormone (GH). Despite a multimodality approach involving surgery, radiation, dopamine agonists and somatostatin agonists the management of acromegaly in some patients has remained a challenge. Although, octreotide and lanreotide are the mainstay for medical therapy in acromegaly, their relatively short biological half-life, pharmacokinetic profiles and side effects emphasize the need for a new generation of somatostatin analogs with improved therapeutic index. The antisecretory activity of somatostatin is mediated by high affinity somatostatin receptors (which belong to five subtypes) on pituitary adenomas. The suppression of GH secretion by somatostatin is mediated primarily by sst2 and sst5, via inhibition of cAMP and intracellular calcium levels. Additionally, the inhibition of exocytosis and cell proliferation by ssts also contributes to the antisecretory activity of somatostatin. Sst2 and sst5 are expressed in almost all GH-secreting adenomas. The present review summarizes the in vitro and in vivo GH-inhibitory activity of novel somatostatin agonists and their potential applications in the therapy of acromegaly. The signaling networks underlying somatostatin receptor subtypes particularly sst2, sst5 and sst1 in mediating the antisecretory activity of somatostatin agonists have been discussed. A brief summary of the clinical efficacy of currently available somatostatin agonists in acromegaly patients is also presented. Novel somatostatin analogs like PTR3173, ASS-52, SOM230, KE108 and bispecific agonists (analogs targeting more than one cellular receptor) like BIM-23244 and BIM-23A387 represent a new generation of GH-inhibitory agents, which may lead to improved therapeutic strategies in acromegaly.
Keywords: acromegaly